Embryonic blood-cerebrospinal fluid barrier formation and function - Bueno, David; Parvas, Maryam; Hermelo, Ismaïl; Garcia-Fernàndez, Jordi (Frontiers in Neuroscience, 2014)
During embryonic development and adult life, brain cavities and ventricles are filled with cerebrospinal fluid (CSF). CSF has attracted interest as an active signaling medium that regulates brain development, homeostasis and disease. CSF is a complex protein-rich fluid containing growth factors and signaling molecules that regulate multiple cell functions in the central nervous system (CNS). The composition and substance concentrations of CSF are tightly controlled. In recent years, it has been demonstrated that embryonic CSF (eCSF) has a key function as a fluid pathway for delivering diffusible signals to the developing brain, thus contributing to the proliferation, differentiation and survival of neural progenitor cells, and to the expansion and patterning of the brain. From fetal stages through to adult life, CSF is primarily produced by the choroid plexus. The development and functional activities of the choroid plexus and other blood–brain barrier (BBB) systems in adults and fetuses have been extensively analyzed. However, eCSF production and control of its homeostasis in embryos, from the closure of the anterior neuropore when the brain cavities become physiologically sealed, to the formation of the functional fetal choroid plexus, has not been studied in as much depth and remains open to debate. This review brings together the existing literature, some of which is based on experiments conducted by our research group, concerning the formation and function of a temporary embryonic blood–CSF barrier in the context of the crucial roles played by the molecules in eCSF.